Factors affecting purchase and repurchase intention of Samsung Galaxy Smartphone in Melaka / Muhammad Fahmi Nazarudin - Nazarudin, Muhammad Fahmi (Faculty of Business and Management, 2018)
Samsung is one of the leading manufacturer and top seller in the world in the smartphone industry. Despite all the problems encountered by Samsung corporation, Samsung is still managed to maintain their performance and ranking as one of the giant in the smartphone industry. Throughout this study, the researcher will investigate what are the factors that can influence the purchase intention of Samsung Galaxy smartphone in Melaka. The independent variables are price, brand image, and features while the dependent variable is the purchase intention. A set of 200 questionnaire were distributed to the Samsung users living in Melaka and the data collected will be analyzed using Statistical Package for Social Sciences (SPSS) version 23. The findings shows that two out of three hypotheses were accepted. Price is rejected while brand image and features are accepted.